Gambaran Motorik Anak Yang Menggunakan Alat Permainan Edukatif Di TK DCC 2019 - Mohamad Rheza Firmansyah Zamzami; Festy Ladyani Mustofa; Supriyati (ARTERI : Jurnal Ilmu Kesehatan, 2020)
Child development‘s delay in Indonesia based on the Indonesia Ministry of Health was 16% of a total toddler in Indonesia. The various factors affecting the child’s development, such as the stimulation of the educative game instrument (EGI). Increase of the use of EGI in other countries proportional to the child’s development aspect but not in Indonesia. To know the overview of the motor development level of preschool-aged children towards the educative game instrument at Dian Cipta Cendekia (DCC) Global School Kindergarten 2019. A descriptive quantitative study by using an observational approach was performed. The data were collected using a review of the school report, the use of the EGI, and the ability to follow the commands based on Denver II categories. This research was done during November 2019. There were six samples from class b taken using a total sampling method. 1 of 6 children failed by following 1 of 12 activities based on Denver II. One of them couldn’t use the climbing frames properly, and based on the school report, 1 of 6 children stated as not developing yet by knowing the traffic sign. The level of using EGI proportional to the child’s development aspect. The frequency distribution of the use of EGI shown 91,7% good. An overview of motor development level based on school report shown 54,2% normal development and 100% normal by Denver II.